Strategi Inovatif Pojok Perpustakaan Dan Rumah Pintar Dalam Pengembangan Pendidikan Formal Dan Non Formal Di Desa Penatarsewu Tanggulangin - Ragillia Fitri Nur Janah; Muhammad Fahrul Muttaqin; M. Alvan Rizki (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Penatarsewu is a village in Tanggulangin sub-district, Sidoarjo district. Penatarsewu village is known as the smoke village. The geographical location of Penatarsewu village is densely populated, located quite far from the city center about 12.9 KM. The development of technology and education that is increasingly advanced is expected to help residents to use the facilities as well as possible. For this reason, we UMSIDA KKN-T Group 27 students provide assistance and innovate to help develop the level of understanding of education to the community, especially for minors. The innovation strategy provided is by opening a "Smart House" program whose contents help underage children to learn the science of education both formal and non-formal education. Apart from the learning program, we as students also provide additional facilities at AISIYAH Kindergarten in the form of a "Library Corner". With the library corner, it is hoped that it can foster a new enthusiasm for minors to prefer reading books, both learning books and story books that can provide new knowledge and experiences for children. So that this service is one of the platforms that aims to help educate the younger generation of Penatasewu village in improving the quality and quantity of education for minors through formal education programs in kindergarten and non-formal education in the learning forum "Rumah Pintar".